Fungus infected atrial myxoma: A rare cause of infective endocarditis and chordae rupture - Özmen, Gökhan; Doganay, Kübra; Ari, Hasan; Dasli, Tolga; Tutuncu, Ahmet; Melek, Mehmet; Demir, Mehmet; Tenekecioglu, Erhan (Asian Journal of Medical Sciences, 2014)
Case reports are increasing about infected myxomas. Infection with bacteria is relatively much more but fungus infected atrial myxomas are exteremely rare and may complicate the disease course. As our knowledge this is the first fungus infected myxoma report in Turkish population. DOI: http://dx.doi.org/10.3126/ajms.v6i3.11045 Asian Journal of Medical Sciences Vol.6(3) 2015 81-83